2011
DOI: 10.1089/end.2010.0213
|View full text |Cite
|
Sign up to set email alerts
|

Shockwave Lithotripsy in Patients with Horseshoe Kidney: Determinants of Success

Abstract: Patients with HSK appear to have lower success and stone-free rates after SWL than patients with normal kidneys. This likely has to do with factors such as greater skin-to-stone distance (particularly for calyceal stones) and restricted urinary drainage. SWL may be offered to patients with a HSK once limitations in stone clearance have been considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…[10][11][12] Anatomic factors associated with concomitant metabolic disorders contribute to this condition, and make endoscopic treatment difficult. [13][14][15] PCNL is the chosen option for the treatment of anomalous kidney stones, especially for stones larger than 20 mm, with stone-free rates between 80 and 90%. [16][17][18][19][20] The success of the procedure is impaired by features such as renal pelvis and anteriorly positioned calyces, vascular abnormalities and different anatomical relationships with adjacent organs, which increases the risk of perioperative complications and the difficulty of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Anatomic factors associated with concomitant metabolic disorders contribute to this condition, and make endoscopic treatment difficult. [13][14][15] PCNL is the chosen option for the treatment of anomalous kidney stones, especially for stones larger than 20 mm, with stone-free rates between 80 and 90%. [16][17][18][19][20] The success of the procedure is impaired by features such as renal pelvis and anteriorly positioned calyces, vascular abnormalities and different anatomical relationships with adjacent organs, which increases the risk of perioperative complications and the difficulty of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…1 Tunc et al, 24 in turn, reported a rate of 92% for stones < 10 mm, but 34% for those greater than 30 mm. 3 Coupled with lower efficiency of ESWL in eliminating larger stones, Ray et al 13 has pointed out that 51% of their patients needed an additional procedure, but that little improvement occurred after the second session, revealing a limitation in the number of attempts that could be made.…”
Section: Discussionmentioning
confidence: 99%
“…Altered pyelocalyceal system anatomy and high ureteropelvic junction position lead to relatively poor results of SWL and retrograde intrarenal surgery. Some experts reported that PCNL had acceptable results in HSK with renal stones; its safety and efficacy resembled the anatomy of a normal kidney [4,7,8]. Desai et al [9] treated patients with staghorn calculi in a HSK by PCNL.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde in renal surgery (RIRS) had lower stone-free rate (SFR) than PCNL for the HSK's malformed anatomical structures; it was difficult for the stone fragments to complete drain and pass through the urinary tract. Some patients with complexity and large renal stones need second stage surgery [5,7]. In such cases, instead of open surgery, laparoscopic pyelolithotomy could be performed to deal with this clinical condition when ESWL and PCNL have both failed.…”
Section: Introductionmentioning
confidence: 99%
“…Failure of SWl has been associated with focusing difficulties due to anteriorly localized renal pelvis, medial calyces masked with vertebra, a requirement for the supine position, renal malrotations, ectopic renal pelvis, fused lower pole, high insertion ureter, stasis due to vascular variations, drainage disorders, stone size, stone localization and BMI [6][7][8].…”
Section: Horseshoe Kidneysmentioning
confidence: 99%